2017
DOI: 10.12965/jer.1734962.481
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long or short duration stimulus during high-intensity interval training on physical performance, energy intake, and body composition

Abstract: To compare the effects of 6 weeks of long or short high-intensity interval training (long- or short-HIIT) on body composition, hunger perception, food intake and rating of perceived exertion (RPE). Twenty previously untrained women (25±5 years) were randomly assigned to do a long-HIIT (n=10) or a short-HIIT (n=10). The long-HIIT group performed fifteen 1-min bouts at 90% of maximum heart rate (HRmax), interspersed by 30-sec active recovery (60% HRmax). The short-HIIT group performed forty-five 20-sec bouts at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
4
13
0
1
Order By: Relevance
“…Our data shows improvements in body composition parameters following a 12-week of HIIT in males with obesity. These ndings are in line with the previous studies showing the bene cial effects of HIIT on body composition in individuals with overweight/obesity [36,37]. Moreover, a recent meta-analysis concluded that HIIT is a timee cient alternative that induces greater reductions in body fat percentage compared to traditional exercise programs in adults with [37].…”
Section: Discussionsupporting
confidence: 91%
“…Our data shows improvements in body composition parameters following a 12-week of HIIT in males with obesity. These ndings are in line with the previous studies showing the bene cial effects of HIIT on body composition in individuals with overweight/obesity [36,37]. Moreover, a recent meta-analysis concluded that HIIT is a timee cient alternative that induces greater reductions in body fat percentage compared to traditional exercise programs in adults with [37].…”
Section: Discussionsupporting
confidence: 91%
“…It was concluded that the training frequency is associated with fat mass loss. Accordingly, an increase in free-fat mass after a HIIT period was reported by other authors [13,32], even though a limitation of these two studies was that they focused on overweight and obese women. Finally and along the same lines, HIIT has been demonstrated to be efficient in improving body composition in normal-weight subjects [33,34].…”
Section: Body Compositionmentioning
confidence: 84%
“…HIIT can be manipulated by several different parameters, such as duration and intensity of work phases, number of series and repetitions, work to rest ratios, etc. ; indeed, distinct protocols can differently affect the adaptive responses to the exercise [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, its effect on the cardiovascular system would not be expected to be adequate in counteracting cardiovascular deconditioning (Belin de Chantemele et al, 2004). Interestingly, a large body of data generated on Earth shows that high intensity interval training (HIIT) fulfills all these needs (Alves et al, 2017; Winding et al, 2018). The benefits of HIIT to cardiometabolic health have been extensively studied during the past decade and detailed in many reviews (Bird and Hawley, 2012; Gibala et al, 2012, 2014; MacInnis and Gibala, 2017; Wormgoor et al, 2017).…”
Section: Where Do We Go From Here?mentioning
confidence: 99%